Hubungan Gaya Hidup dengan Kejadian Hipertensi pada Usia Dewasa di Kelurahan Subangjaya Wilayah Kerja Puskesmas Sukabumi Kota Sukabumi - Nunung Liawati; Tri Lusiani Maharani Sidik (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
Hypertension is a disease that can cause complications towards other organs, and it will be more dangerous if the sufferer is classified as an adult. From 15 health centers in Sukabumi, Sukabumi Health Center occupies high number of hypertension cases at adult age about 706 or 16.3%. The purpose of this study is to determine the correlation between lifestyle and hypertension at adult age. Hypertension is a condition when blood pressure systole is 140 mmHg or higher and diastolic blood pressure is 90 mmHg or higher. One of the factors that influence the incidence of hypertension is lifestyle. This study used the type of correlational research with cross sectional approach. The population was 8,403 people with 383 people as the sample. Cluster Random Sampling was conducted to take the samples. The result of validity test of the lifestyle variable on 20 items was valid since the reliability was 0.787. The statistical analysis used Chi Square. The results showed that healthy lifestyles was 52.5%, the incidence of non-hypertensive hypertension was 50.4%. There was correlation between lifestyle and the incidence of hypertension at adult age because it has p-value of 0.00.